APPLICATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES FOR THE CONTROL OF THE TECHNICAL STATE OF VEHICLES IN A TRANSPORT STREAM - N. S. Jankevich (Цифровая трансформация)
The article deals with the specifics of the application of information technologies in the transport sphere. The importance of improving the safety of the vehicle operation is substantiated, and possible ways of solving this issue are presented. The article contains a sequence of analysis of the reliability of an internal combustion engine, which is considered as a complex multi-level system. As a methodological basis for constructing computational algorithms of the system of preventive diagnostics, a systematic approach was chosen. An algorithm for the development of a mathematical apparatus for a diagnostic system that is part of an "intelligent" transport system is presented. A model of the engine diagnostic system was developed. The data obtained with its help were used as the basis for the functioning of the vehicle failure prediction system.